Genetic and behavioral modification of hemoglobin and iron status among first‐time and high‐intensity blood donors. Issue 4 (12th March 2020) - Mast, Alan E.; Langer, John C.; Guo, Yuelong; Bialkowski, Walter; Spencer, Bryan R.; Lee, Tzong‐Hae; Kiss, Joseph; Cable, Ritchard G.; Brambilla, Donald; Busch, Michael P.; Page, Grier P.; ,
ABSTRACT: BACKGROUND: Some people rapidly develop iron deficiency anemia following blood donation, while others can repeatedly donate without becoming anemic. METHODS: Two cohorts of blood donors were studied. Participants (775) selected from a 2‐year longitudinal study were classified into six analysis groups based on sex, donation intensity, and low hemoglobin deferral. Associations with iron supplement use, cigarette smoking, and four genetic variants of iron metabolism were examined at enrollment and with longitudinal regression models. An unbiased assessment of genetic variability and ability to repeatedly donate blood without experiencing low hemoglobin deferral was conducted on participants (13, 403) in a cross‐sectional study who were examined by genome wide association (GWA). RESULTS: Behaviors and genetic variants were associated with differences in hemoglobin and ferritin change following repeated donation. At least weekly iron supplement use was associated with improved status in first‐time donors, while daily use was associated with improved status in high‐intensity donors. Cigarette smoking was associated with 0.5 g/dL increased hemoglobin in high‐intensity donors. A736V in TMPRSS6 was associated with a rapid drop in hemoglobin and ferritin in first‐time females following repeated donation. Conversely, the protective TMPRSS6 genotype was not enriched among high‐intensity donors. H63D in HFE was associated with increased hemoglobin in female high‐intensity donors. However, no differences in genotype between first‐time and high‐intensity donors were found in GWA analyses. CONCLUSION: Behavioral and genetic modifiers contributed to first‐time donor hemoglobin and iron status, while iron supplement use was more important than underlying genetics in high‐intensity donors.